Characterization of plasmids mediating carbapenem resistance in Klebsiella pneumoniae in Pretoria, South Africa - Mbelle, Nontombi (University of Pretoria, 2024)
Dissertation (MSc (Medical Microbiology))--University of Pretoria, 2020.